2019
DOI: 10.1080/19490976.2019.1618173
|View full text |Cite
|
Sign up to set email alerts
|

The ‘in vivo lifestyle’ of bile acid 7α-dehydroxylating bacteria: comparative genomics, metatranscriptomic, and bile acid metabolomics analysis of a defined microbial community in gnotobiotic mice

Abstract: Gaskins (2020) The 'invivo lifestyle' of bile acid 7αdehydroxylating bacteria: comparative genomics, metatranscriptomic, and bile acid metabolomics analysis of a defined microbial community in gnotobiotic mice,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
138
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(146 citation statements)
references
References 74 publications
(111 reference statements)
6
138
2
Order By: Relevance
“…Ninety‐five percent of them are transported back to the liver via a process known as enterohepatic circulation. The remaining 5% escape this process and are metabolized by gut bacteria (eg, Clostridium hylemonae and Clostridium hiranonis ), primarily in the colon, into secondary bile acids, including lithocholic acid and DCA . A number of animal studies in the past few decades have shown the carcinogenic effect of DCA in gastroenterological organs .…”
Section: Deoxyxcholic Acid Accelerates Colorectal Cancer Carcinogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…Ninety‐five percent of them are transported back to the liver via a process known as enterohepatic circulation. The remaining 5% escape this process and are metabolized by gut bacteria (eg, Clostridium hylemonae and Clostridium hiranonis ), primarily in the colon, into secondary bile acids, including lithocholic acid and DCA . A number of animal studies in the past few decades have shown the carcinogenic effect of DCA in gastroenterological organs .…”
Section: Deoxyxcholic Acid Accelerates Colorectal Cancer Carcinogenesismentioning
confidence: 99%
“…Bacteria related to colitis-associated CRC Enterotoxigenic Bacteroides fragilis 8 Adherent-invasive Escherichia coli 9 Genotoxic compound producing bacteria Pks + Escherichia coli strains (colibactin) 13 Clostridium hylemonae (deoxycholic acid) 12 Clostridium hiranonis (deoxycholic acid) 12 Bacteria related to non-colitis-associated CRC Fusobacterium nucleatum 10,11,[14][15][16]19,20 Parvimonas micra 20,26 Peptostreptococcus stomatis 19,20 Peptostreptococcus anaerobius 20,25 Atopobium parvulum 28 Actinomyces odontolyticus 28,30 factors in carcinogenesis, or whether they are a result of microbial adaptation to the tumor environment. Nevertheless, CRC-associated microbiota are currently globally accepted as CRC screening biomarkers that can be used as an alternative for the fecal occult blood test.…”
Section: Ta B L E 1 Association Between Gut Bacteria and Colorectal Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Several enzymes within the bai operon are capable of completing the steps in this transformation, including the bile acid transporter BaiG, the bile acid 7α-dehydratase BaiE, and the flavoprotein BaiN (13, 1719). While regulation of the bai operon has yet to be completely elucidated, in vitro studies show that CA upregulates genes in the bai operon and DCA downregulates them in C. scindens ATCC 35704, C. hylemonae , and C. hiranonis (20, 21).…”
Section: Introductionmentioning
confidence: 99%
“…Because bile [8] contains a large amount of water as well as bile pigments, bile salts, cholesterol, lecithin, fatty acids, inorganic salts, and other ingredients, our research team designed a superhydrophobic, oleophobic coating, which is intended to be used on the inner and outer walls of a bile duct stent. It was assumed that since the coating has a bile-repellent effect on polar groups (e.g., water, ions, and polar amino acids) and non-polar groups (e.g., lipids and non-polar amino acids), it would repel bile.…”
Section: Introductionmentioning
confidence: 99%